1999
DOI: 10.1016/s0168-9002(99)00043-1
|View full text |Cite
|
Sign up to set email alerts
|

The SELEX phototube RICH detector

Abstract: In this article, construction, operation, and performance of the RICH detector of Fermilab experiment 781 (SELEX) are described. The detector utilizes a matrix of 2848 phototubes for the photocathode to detect Cherenkov photons generated in a 10 m Neon radiator. For the central region an N 0 of 104 cm −1 , corresponding to 13.6 hits on a β = 1 ring, was obtained. The ring radius resolution measured is 1.6 %.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 11 publications
(12 reference statements)
0
30
0
4
Order By: Relevance
“…The following section summarizes the principle of operation of RICH counters, and the description and construction of the MIPP RICH as described in [16,15,14].…”
Section: Rich Detectormentioning
confidence: 99%
See 4 more Smart Citations
“…The following section summarizes the principle of operation of RICH counters, and the description and construction of the MIPP RICH as described in [16,15,14].…”
Section: Rich Detectormentioning
confidence: 99%
“…Both tests showed that the window material is both gas and light tight [16]. Each mirror was polished such that an image size of a point source illuminating the mirror was less than 1 mm.…”
Section: Entrance and Exit Windowsmentioning
confidence: 99%
See 3 more Smart Citations